Correction: Pollen morphology of cucurbitaceae using microscopic techniques for accurate taxa identification - Haleema Sadia; Khafsa Malik; Rahmatullah Qureshi; Khalid Mehmood; Khushdil Khan; Ahmad Hassan; Shabir Ahmad; Hussain Shah; Huma Gul; Jawaher Alkahtani; Bandar Mohsen Almunqedhi; Rashid Iqbal; et al. (Genetic Resources and Crop Evolution, 2025)

Pharmacological evaluation of phage-antibiotic synergism against clinical isolates of multi-drug resistant Staphylococcus aureus in a burn-induced infection mouse model - Syed Damin Abbas Hamdani; Mustafeez Mujtaba Babar; Huma Sajjad; Alvina Gul; Mudassira Zahid; Tausif Ahmed Rajput; Aneeqa Noor; Madiha Ahmed; John J. Dennehy (Brazilian Journal of Microbiology, 2025)

A comprehensive assessment of heavy metal pollution in flood-affected areas in Pakistan: a case study of the 2022 superflood through pollution and water quality indices - Nida Gul; Nazish Huma Khan; Nasir Mehmood; Muhammad Idrees; Carlos A. T. Toloza; Eman Alzahrani; Rachel Ann Hauser-Davis; Sarzamin Khan (Sustainable Water Resources Management, 2025)

Palynological research and taxonomic implications of selected bee forage plants using microscopic techniques for accurate taxa identifications - Ateef Ullah; Mushtaq Ahmad; Naila Mukhtar; Shabir Ahmad; Hussain Shah; Faran Durrani; Huma Gul; Muhammad Abdullah; Nasira Bibi; Nabeel Ur Rehman; Reem M. Aljowaie; Abd El-Zaher M. A. Mustafa; et al. (Genetic Resources and Crop Evolution, 2025)

Pollen morphology of cucurbitaceae using microscopic techniques for accurate taxa identification - Haleema Sadia; Khafsa Malik; Rahmatullah Qureshi; Khalid Mehmood; Khushdil Khan; Ahmad Hassan; Shabir Ahmad; Hussain Shah; Huma Gul; Jawaher Alkahtani; Bandar Mohsen Almunqedhi; Rashid Iqbal; et al. (Genetic Resources and Crop Evolution, 2025)

Impact of pH on the growth and nutritional profile of Lemna minor L. as a sustainable alternative for Pakistan’s feed sector - Hafiz Ullah; Bakhtiar Gul; Haroon Khan; Khushnood ur Rehman; Ishfaq Hameed; Umar Zeb; Sohaib Roomi; Zill-E-Huma (Aquaculture International, 2023)

Erratum to: Spatio-temporal changes in the six major glaciers of the Chitral River basin (Hindukush Region of Pakistan) between 2001 and 2018 - Jawaria Gul; Sher Muhammad; Shi-yin Liu; Siddique Ullah; Shakeel Ahmad; Huma Hayat; Adnan Ahmad Tahir (Journal of Mountain Science, 2020)
The article Spatio-temporal changes in the six major glaciers of the Chitral River basin (Hindukush Region of Pakistan) between 2001 and 2018, written by Jawaria GUL, Sher MUHAMMAD, LIU Shi-yin, Siddique ULLAH, Shakeel AHMAD, Huma HAYAT and Adnan Ahmad TAHIR, was originally published Online First without Open Access. After publication in volume 17, issue 3, page 572-587, the author decided to opt for Open Choice and to make the article an Open Access publication. Therefore, the copyright of the article has been changed to © The Author(s) 2020 and the article is forthwith distributed under the terms of the Creative Commons Attribution 4.0 International License (http://creativecommons.org/licenses/by/4.0/), which permits use, duplication, adaptation, distribution and reproduction in any medium or format, as long as you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons license, and indicate if changes were made. The original version of this article has been revised due to a retrospective Open Access order.

Spatio-temporal changes in the six major glaciers of the Chitral River basin (Hindukush Region of Pakistan) between 2001 and 2018 - Jawaria Gul; Sher Muhammad; Shi-yin Liu; Siddique Ullah; Shakeel Ahmad; Huma Hayat; Adnan Ahmad Tahir (Journal of Mountain Science, 2020)
Glaciers in the northern Pakistan are a distinctive source of freshwater for the irrigation, drinking and industrial water supplies of the people living in those regions and downstream. These glaciers are under a direct global warming impact as indicated in many previous studies. In this study, we estimated the glacier dynamics in terms of Equilibrium Line Altitude (ELA), mass balance and the snout position variation using remote sensing data between 2001 and 2018. Six glaciers, having area ≥ 20 km 2 each, situated in the Chitral region (Hindukush Mountains) were investigated in this study. Digital Elevation Model (DEM) and available cloud-free continuous series of Landsat and Sentinel the entire study area was a retreat of -231 ± 140 m. No obvious relationship was found between the glacier variation trends and the available gauged climatic data possibly due to the presence of debris cover in ablation zones of all the studied glaciers which provides insulation and reduces the immediate climatic effects.

Deciphering the growth, organic acid exudations, and ionic homeostasis of Amaranthus viridis L. and Portulaca oleracea L. under lead chloride stress - Muhammad Tariq Javed; Muhammad Sohail Akram; Noman Habib; Kashif Tanwir; Qasim Ali; Nabeel Khan Niazi; Huma Gul; Naeem Iqbal (Environmental Science and Pollution Research, 2018)